THE CREATION OF THE ZONES OF PRIORITY DEVELOPMENT AS AN INSTRUMENT OF INVESTMENTS ATTRACTION IN THE RUSSIAN FEDERATION REGIONS INDUSTRIAL INFRASTRUCTURE DEVELOPMENT - F. Sharipov; A. Sadkov (Вестник университета, 2019)
The article describes the perspectives of development of industrial infrastructure of the Russian Federation regions by creation of the zones of priority development. The purposes of creation of the zones of priority development, the principles of functioning and fundamental differences from special economic zones were considered. The already created the zones of priority development short characteristic and the further perspectives of their development were given. The connection of creation and development of the zones of priority development with the formation of innovative territorial clusters was tracked.